Bacterial Contaminants and Antibiogram of Ghana Paper Currency Notes in Circulation and Their Associated Health Risks in Asante-Mampong, Ghana - Denis Dekugmen Yar (International Journal of Microbiology)
Transmission of pathogens through currency notes has become very relevant in today’s world due to COVID-19 pandemic. This study profiled microbial flora and their antibiotic activities from Ghana paper currency (GH¢) notes in circulation in Mampong Municipal of Ashanti Region, Ghana. The study employed a cross-sectional design to assess bacterial contaminants and their antibiotic activities from January to May 2019. A total of 70 GH¢ notes consisting of 15 each of GH¢1, GH¢2, and GH¢5; 10 each of GH¢10 and GH¢20; and 5 of GH¢50 were randomly sampled from persons at different shops, canteens, and commercial drivers. The surfaces of each GH¢ note were gently swabbed, and tenfold serial dilutions made were inoculated on plate count agar (PCA), MacConkey agar, mannitol salt agar, and deoxycholate citrate agar. The study used appropriate laboratory and biochemical tests for bacterial identification. SPSS-IBM version 16.0 was used to analyze the data. Of the 70 GH¢ notes studied, 97.1% were contaminated with one or more bacterial isolates. Mean counts on PCA ranged between 3.2 cfu/ml × 105 and 4.7 cfu/ml × 105 on GH¢ notes. Of 124 bacteria isolated, 34 (27.4%), 30 (24.2%), 22 (17.7%), 17 (13.7%), 13 (10.5%), and 8 (6.5%) were from GH¢1, GH¢2, GH¢10, GH¢5, GH¢20, and GH¢50, respectively (p<0.05). Bacterial isolates were Escherichia coli (28.23%), Staphylococcus aureus (16.94%), coagulase-negative Staphylococcus (16.13%), Klebsiella species (11.29%), Salmonella species (9.68%), Shigella species (8.87%), Pseudomonas aeruginosa (5.65%), and Proteus species (3.23%). GH¢ notes had 25.81%, 20.16%, 19.35%, 17.74%, and 16.94% from meat shops, commercial drivers, canteens, grocery shops, and vegetable shops, respectively. All bacteria were 100% resistant to erythromycin, 87.5% to tetracycline, chloramphenicol, and cotrimoxazole, 75% to vancomycin, while 87.50% sensitive to amikacin. The GH¢ notes were heavily colonized with potential pathogens, which are resistant to most commonly used antibiotics and could pose a health threat to users during commercial transactions.